Relationship between Intellectual Capital and Corporate Profitability - Jannati Tangngisalu (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to empirically evaluate the partial effect of Intellectual Capital Profitability. This research is quantitative, with hypotheses derived using the Resources-Based Theory and supported by prior studies employing the same variables. Listed Property and Real Estate Companies on the Indonesia Stock Exchange are the focus of this study. Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), and Profitability are research variables (ROI). The data utilized is secondary data published in the company's financial statements. 168 samples were collected from 42 property and real estate companies on the Indonesia Stock Exchange. Data analysis utilizing descriptive statistical techniques and panel data regression with the assistance of eviews. In addition, to maintain the normality of the data, the Classical Assumption test is employed in this study. The findings indicated that Intellectual Capital with VACA, VAHU, and STVA assessments positively and statistically significant impact on Profitability (ROI) in Property and Real Estate companies listed on the Indonesia Stock Exchange. The profitability of the company can be increased by optimizing Intellectual Capital. Intellectual Capital that cannot be optimized will have a negative impact on the company's profitability.